2 - The University as a Site of Knowledge: The Role of Basic Research - Chachage, Chachage Seithy L. (Journal of Higher Education in Africa, 2006)
This paper extrapolates from the tensions between the University of Dar es Salaam Academic Staff Assembly (UDASA) and the university administration to make a case for academic freedom in Tanzania in particular and Africa in general. It draws on two key statements on academic freedom in Africa – the Dar es Salaam Declara- tion on Academic Freedom and Social Responsibility of Academics (1990) and the Kampala Declaration on Intellectual Freedom and Social Responsibility (1991), to discuss the role of basic research in the university as a site for knowledge produc- tion. The paper argues that the quest for academic freedom is only meaningful if universities renew their commitment to the public good. Only by fulfilling the pub- lic trust as weavers of the social fabric and upholders of the highest ethical dimen- sions of human life can universities reclaim their position in society and the world at large.